PEMBUNUHAN SEBAGAI PENGHALANG HAK WARIS PERSPEKTIF MADZHAB MALIKI - Ahmad Arif Noeris; Istikharoh Istikharoh (Jurnal Al-Wasith : Jurnal Studi Hukum Islam, 2023)
This research aims to 1). find out how the Maliki Madzhab views murder as an obstacle to inheritance rights; 2). Understand the method of extracting arguments according to the Maliki Madzhab in the case of murder which does not become an obstacle to inheritance rights. The research method used is a type of library research with the object of research being the legal view of killing in relation to inheritance rights, according to the views of the Maliki Madzhab, digging from library sources, in the form of books, scriptures, encyclopedic journals, papers. -Then from these sources we collected the opinions of the Islamic School of Jurisprudence after that we selected the opinions in the Maliki School of thought regarding murder as a barrier to inheritance. The results of the research are that according to the Maliki school of thought, there is only one type of murder that prohibits a person from obtaining an inheritance, namely the type of murder that is carried out intentionally (al-qatl al-'amd) which is based on hostility, whether carried out directly or indirectly. Meanwhile, other types of murder still receive inheritance even though there is a re-division in terms of whether they can accept diyat or not.